Corruption prevention practices and tax avoidance - Mohamed Elmagrhi (British Accounting and Finance Association)
This paper examines the impact of corruption prevention practices on tax avoidance, from a neo-institutional theoretical perspective. Our study also contributes to the existing corruption and tax literature by considering the moderating effect of corporate board characteristics on the association between corruption prevention practices and tax avoidance. Based on a sample of FTSE 350 UK listed firms, our findings illustrate that firm’s commitment to good anti-corruption practices is linked with lower tax avoidance.